An Embedded Reconfigurable IP Core with Variable Grain Logic Cell Architecture. (14th September 2008) - Amagasaki, Motoki; Yamaguchi, Ryoichi; Koga, Masahiro; Iida, Masahiro; Sueyoshi, Toshinori
Abstract : Reconfigurable logic devices (RLDs) are classified as the fine-grained or coarse-grained type based on their basic logic cell architecture. In general, each architecture has its own advantage. Therefore, it is difficult to achieve a balance between the operation speed and implementation area in various applications. In the present paper, we propose a variable grain logic cell (VGLC) architecture, which consists of a 4-bit ripple carry adder with configuration memory bits and develop a technology mapping tool. The key feature of the VGLC architecture is that the variable granularity is a tradeoff between coarse-grained and fine-grained types required for the implementation arithmetic and random logic, respectively. Finally, we evaluate the proposed logic cell using the newly developed technology mapping tool, which improves logic depth by 31% and reduces the number of configuration data by 55% on average, as compared to the Virtex-4 logic cell architecture.